Hot Melt Extrusion Technique for Developing Pharmaceutical Co-crystals: A Review - Rathi, Ritu; Sanshita; Singh, Inderbir (Drug Delivery Letters, 2024)
Background: In the era of pharmaceutical research and development, the most challenging aspect is to enhance the physicochemical properties of drugs. Hot Melt Extrusion (HME) is a solvent-free, one-step, continuous, scalable, and industrially feasible method for developing pharmaceutical co-crystals. Co-crystallization, as a technique, has gained significant attention for its potential to modify various physicochemical properties of drugs like solubility, stability, compressibility, permeability, taste masking, and therapeutic efficacy. Methods: We determine the characteristic features of HME and explore published literature using the keywords, HME, co-crystals, and PAT, in databases, such as PubMed, Google Scholar, ScienceDirect, and Research Gate. Results: The present review embarks on a detailed journey through the multifaceted domain of HME and its pivotal role in co-crystal development. The process parameters, such as temperature, extruder type, screw configuration, screw speed, and feed rate, are involved in determining the characteristics of the co-crystals produced. Additionally, the review explores the role of materials, including Active Pharmaceutical Ingredients (APIs), plasticizers, polymers, and other pharmaceutical aids, underlining their impact on co-crystal development. The existing literature on HME and its application for pharmaceutical co-crystal production is comprehensively surveyed. Conclusion: The review highlights the utility of Process Analytical Technology (PAT) in realtime process control. The role of HME in the future of pharmaceutical co-crystal development is discussed, making this review essential for researchers and industry professionals alike.
Keywords: co-crystals